2010
DOI: 10.3109/08820139.2010.503766
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi Chuan Increases Circulating Myeloid Dendritic Cells

Abstract: Dendritic cells, the most potent antigen-presenting cells linking innate and adoptive immunity, are thought to be important targets of immune modulators such as exercise. We examined the effect of Tai Chi Chuan (TCC) on dendritic cells. TCC practitioners were further divided to high-level practitioners (TCC-H) and low-level practitioners (TCC-L). The quantities of myeloid and plasmacytoid dendritic cells were estimated by flow cytometry. We examined parameters including age, body weight, body length, body fat,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…Another possibility is that the EE may induce NK cell activity previously described as absent in a VSV encephalitis murine model maintained in standard cages [15]. In line with these views, voluntary exercise such as that observed in an EE increases the number of blood dendritic cells [49], [50], [51], [52] and NK cells [6]. Because we did not use selective markers for other immune cells such as recruited monocytes/macrophages [53], dendritic cells [15], or NK cells [54], it remains to be confirmed whether these cells are associated or not with the immune response induced by Piry virus infection and whether or not EE affects their distribution and number.…”
Section: Discussionmentioning
confidence: 87%
“…Another possibility is that the EE may induce NK cell activity previously described as absent in a VSV encephalitis murine model maintained in standard cages [15]. In line with these views, voluntary exercise such as that observed in an EE increases the number of blood dendritic cells [49], [50], [51], [52] and NK cells [6]. Because we did not use selective markers for other immune cells such as recruited monocytes/macrophages [53], dendritic cells [15], or NK cells [54], it remains to be confirmed whether these cells are associated or not with the immune response induced by Piry virus infection and whether or not EE affects their distribution and number.…”
Section: Discussionmentioning
confidence: 87%
“…When collated this research suggests that performing T'ai chi exercises leads to an improvement of both cell-mediated immunity and antibody response to infection. [28][29][30][31][32][33][34][35][36] However, it should be noted that few studies have demonstrated a unified mechanism behind these improvementsinstead focusing on specific players in the immune response such as circulating myeloid dendritic cells 28,37 or pro-inflammatory CD14 + CD16 + monocytes. 38 Laughter has also been reported to have a surprisingly potent modulating effect on the immune system.…”
Section: Anger Laughter Stress and Tai Chi: Emotion And The Immune mentioning
confidence: 99%
“…Full reports of 36 studies were acquired, and 20 were also excluded because they were uncontrolled observational studies (10), studies with unparallel controls (2), duplicate publications (3), studies using athletes (2), and studies with other outcome measures (3). Sixteen studies published between 1988 and 2010, including 7 RCTs, [11][12][13][14][15][16][17] 4 CCTs, [18][19][20][21] and 5 RCSS, [22][23][24][25][26] met this review's inclusion criteria. These studies were conducted in the United States, 13,14,16,19 Taiwan, 22 and mainland China.…”
Section: Study Descriptionmentioning
confidence: 99%
“…Sixteen studies published between 1988 and 2010, including 7 RCTs, [11][12][13][14][15][16][17] 4 CCTs, [18][19][20][21] and 5 RCSS, [22][23][24][25][26] met this review's inclusion criteria. These studies were conducted in the United States, 13,14,16,19 Taiwan, 22 and mainland China. 11,12,15,17,18,20,21,[23][24][25][26] Seven 7studies 13,14,16,19,22,24,25 were published in English, 8 studies 11,12,15,17,18,21,23,26 were published in Chinese, and the remaining 1 study 20 was a proceeding.…”
Section: Study Descriptionmentioning
confidence: 99%
See 1 more Smart Citation